Ge1−xSnx nanodots crystal nuclei for solid phase crystallization of poly-Si1−x−yGexSny. (1st April 2023) - Shirai, Yusei; Tatsuoka, Hirokazu; Shimura, Yosuke
Abstract: Solid phase crystallization of polycrystalline Si1− x − y Ge x Sn y using Ge1− x Sn x nanodots (Ge1− x Sn x -ND) as crystal nuclei was examined. The effects of the substrate temperature and the ratio of the deposited Ge and Sn on the dot size, the coverage, and the substitutional Sn content in the Ge1− x Sn x -ND were investigated. Lowering the deposition temperature increased the coverage and the substitutional Sn content of the Ge1− x Sn x -ND. Crystallization of Si deposited on the Ge1− x Sn x -ND was confirmed at the deposition temperature of 150 °C. The Si content was higher when Si was deposited on nanodots with higher coverage, and the Si and Sn contents in the poly-Si1− x − y Ge x Sn y layer were estimated to be as high as 36.3% and 4.2%, respectively, after annealing at 225 °C for 30 min.